Epidemiological study of mental disorder in China - HUANG Yueqin (Guangxi Yike Daxue xuebao)
This review introduces the three stages of the development history of mental health epidemiology in China, outlines the diagnosis and classification system of mental disorders, and introduces diagnostic and screening tools for mental disorders such as the Composite International Diagnostic Interview (CIDI) and the Mini International Neuropsychiatric Interview (MINI). Regarding the epidemiological surveys of mental disorders in China and its main results, this review introduces the large-scale epidemiological investigations of mental disorders in China in 1982 and 1993, as well as subsequent investigations in Zhejiang Province, Kunming City, Hebei Province, Shandong Province, Qinghai Province, Tianshui City, etc. It focuses on the "Research on the Burden of Mental Disorders and Health Service Utilization in China" jointly supported by the Ministry of Health and the Ministry of Science and Technology, namely the China mental health survey (CMHS), and analyzes the increasing trend and reasons for the prevalence of most mental disorders in China in the past 30 years. Finally, in the prevention and control of mental disorders, it is necessary to fully utilize population-based research evidence and develop policies and measures that are in line with China's national conditions.